Transformation of land use pattern in the East Borsod coal basin from the beginning of minig industry to the political changes - Sütő, László; Homoki , Erika; Dobány , Zoltán; Rózsa, Péter (Acta Geographica Debrecina Landscape & Environment series, 2016)
Historical geographic studies on land cover may support the understanding of the recent state. Focusing on coal mining, this process was followed and analyzed in the case of the East Borsod Coal Basin from the early 20th century to the political change. The contemporaneous maps and manuscripts concerning the mining were evaluated using geoinformatic techniques. Moreover, digitalized topographic map coming from the early and late period of mining (1924 and 1989, respectively) were analyzed. To determine the degree of human disturbance hemerobic relations and changes of the given land cover patches were quantified on the basis of the maps of the three military surveys, too. It can be stated that montanogenic subtype of an industrialagricultural landscape has been formed in the Bükkhát area. Beside the concentrated artificial surfaces, however, relative dominance of forest forming the matrix of the landscape remained.